Efficacy and safety of adjustable balloons (Proact™) to treat male stress urinary incontinence after prostate surgery: Medium and long‐term follow‐up data of a national multicentric retrospective study. Issue 7 (14th July 2019) - Finazzi Agrò, Enrico; Gregori, Andrea; Bianchi, Daniele; Carone, Roberto; Giammò, Alessandro; Ammirati, Enrico; Giovannelli, Vanni; Romanò, Ai Ling; Martino, Pasquale; Saracino, Alberto; Volpe, Alessandro; Favro, Michele; et al.
Abstract: Aims: Male stress urinary incontinence (SUI) represents a complication after radical prostatectomy or benign prostatic obstruction surgery. The artificial urinary sphincter is considered the standard treatment but interest on minimally invasive devices, such as adjustable balloons, has recently increased. Aim of this study is to evaluate the efficacy and safety of the ProACT system. Methods: In this multicentric retrospective study, we reported the data from nine centers. Patients with SUI who underwent a ProACT device implantation for postoperative SUI and had a minimum follow‐up of 24 months were included. Efficacy was evaluated at the maximum available follow‐up and was assessed utilizing a 24‐hour pad test. Patients were considered: "Dry" if presenting a urine leak weight lower than 8 g at the 24‐hour pad test; "Improved" if presenting a reduction of urine leak higher than 50% (but >8 g/24 hours); "Failure" if presenting a reduction in urine leak lower than 50%. The evaluation included a record of intraoperative and long‐term complications. Results: Safety and efficacy results are reported on 240 patients. 29.6% of patients were dry at 24 months, 37.5% were improved and 32.9% of patients were considered failures. The baseline mean pad weight of 367 g was reduced to 123 g at 24 months. Five‐year follow‐up on 152 patients showed similar efficacy. The complication rate was 22.5%, with the top complication being long‐term balloon failure. Conclusions: ProACT implantation represents a safe and efficacious treatment for male postoperative SUI at both medium and long‐term follow up. 67.1% of patients were dry or improved at 24 months. The majority of complications are low grade.